Step * 1 1 1 1 of Lemma add-rpolynomials


1. : ℕ
2. : ℕ
3. : ℕ1 ⟶ ℝ
4. : ℕ1 ⟶ ℝ
5. : ℝ
6. m ≤ n
7. Σ{(a i) x^i 0≤i≤n} {(a i) x^i 0≤i≤m} + Σ{(a (m 1)) x^m 0≤i≤1})
8. Σ{if i ≤then (a i) (b i) else fi  x^i 0≤i≤n}
{if i ≤then (a i) (b i) else fi  x^i 0≤i≤m}
  + Σ{if 1 ≤then (a (m 1)) (b (m 1)) else (m 1) fi  x^m 0≤i≤1})
9. Σ{if i ≤then (a i) (b i) else fi  x^i 0≤i≤m} {(a i) x^i 0≤i≤m} + Σ{(b i) x^i 0≤i≤m})
10. : ℝ
11. Σ{(a i) x^i 0≤i≤m} v ∈ ℝ
12. v1 : ℝ
13. Σ{(b i) x^i 0≤i≤m} v1 ∈ ℝ
⊢ ((v + Σ{(a (m 1)) x^m 0≤i≤1}) v1)
((v v1)
  + Σ{if 1 ≤then (a (m 1)) (b (m 1)) else (m 1) fi  x^m 0≤i≤1})
BY
(Assert Σ{if 1 ≤then (a (m 1)) (b (m 1)) else (m 1) fi  x^m 0≤i≤m
         1}
         = Σ{(a (m 1)) x^m 0≤i≤1} BY
         ((BLemma `rsum_functionality` THEN Auto) THEN THEN Reduce THEN Auto)) }

1
1. : ℕ
2. : ℕ
3. : ℕ1 ⟶ ℝ
4. : ℕ1 ⟶ ℝ
5. : ℝ
6. m ≤ n
7. Σ{(a i) x^i 0≤i≤n} {(a i) x^i 0≤i≤m} + Σ{(a (m 1)) x^m 0≤i≤1})
8. Σ{if i ≤then (a i) (b i) else fi  x^i 0≤i≤n}
{if i ≤then (a i) (b i) else fi  x^i 0≤i≤m}
  + Σ{if 1 ≤then (a (m 1)) (b (m 1)) else (m 1) fi  x^m 0≤i≤1})
9. Σ{if i ≤then (a i) (b i) else fi  x^i 0≤i≤m} {(a i) x^i 0≤i≤m} + Σ{(b i) x^i 0≤i≤m})
10. : ℝ
11. Σ{(a i) x^i 0≤i≤m} v ∈ ℝ
12. v1 : ℝ
13. Σ{(b i) x^i 0≤i≤m} v1 ∈ ℝ
14. Σ{if 1 ≤then (a (m 1)) (b (m 1)) else (m 1) fi  x^m 0≤i≤1}
= Σ{(a (m 1)) x^m 0≤i≤1}
⊢ ((v + Σ{(a (m 1)) x^m 0≤i≤1}) v1)
((v v1)
  + Σ{if 1 ≤then (a (m 1)) (b (m 1)) else (m 1) fi  x^m 0≤i≤1})


Latex:


Latex:

1.  n  :  \mBbbN{}
2.  m  :  \mBbbN{}
3.  a  :  \mBbbN{}n  +  1  {}\mrightarrow{}  \mBbbR{}
4.  b  :  \mBbbN{}m  +  1  {}\mrightarrow{}  \mBbbR{}
5.  x  :  \mBbbR{}
6.  m  \mleq{}  n
7.  \mSigma{}\{(a  i)  *  x\^{}i  |  0\mleq{}i\mleq{}n\}
=  (\mSigma{}\{(a  i)  *  x\^{}i  |  0\mleq{}i\mleq{}m\}  +  \mSigma{}\{(a  (m  +  i  +  1))  *  x\^{}m  +  i  +  1  |  0\mleq{}i\mleq{}n  -  m  +  1\})
8.  \mSigma{}\{if  i  \mleq{}z  m  then  (a  i)  +  (b  i)  else  a  i  fi    *  x\^{}i  |  0\mleq{}i\mleq{}n\}
=  (\mSigma{}\{if  i  \mleq{}z  m  then  (a  i)  +  (b  i)  else  a  i  fi    *  x\^{}i  |  0\mleq{}i\mleq{}m\}
    +  \mSigma{}\{if  m  +  i  +  1  \mleq{}z  m  then  (a  (m  +  i  +  1))  +  (b  (m  +  i  +  1))  else  a  (m  +  i  +  1)  fi 
        *  x\^{}m  +  i  +  1  |  0\mleq{}i\mleq{}n  -  m  +  1\})
9.  \mSigma{}\{if  i  \mleq{}z  m  then  (a  i)  +  (b  i)  else  a  i  fi    *  x\^{}i  |  0\mleq{}i\mleq{}m\}
=  (\mSigma{}\{(a  i)  *  x\^{}i  |  0\mleq{}i\mleq{}m\}  +  \mSigma{}\{(b  i)  *  x\^{}i  |  0\mleq{}i\mleq{}m\})
10.  v  :  \mBbbR{}
11.  \mSigma{}\{(a  i)  *  x\^{}i  |  0\mleq{}i\mleq{}m\}  =  v
12.  v1  :  \mBbbR{}
13.  \mSigma{}\{(b  i)  *  x\^{}i  |  0\mleq{}i\mleq{}m\}  =  v1
\mvdash{}  ((v  +  \mSigma{}\{(a  (m  +  i  +  1))  *  x\^{}m  +  i  +  1  |  0\mleq{}i\mleq{}n  -  m  +  1\})  +  v1)
=  ((v  +  v1)
    +  \mSigma{}\{if  m  +  i  +  1  \mleq{}z  m  then  (a  (m  +  i  +  1))  +  (b  (m  +  i  +  1))  else  a  (m  +  i  +  1)  fi 
        *  x\^{}m  +  i  +  1  |  0\mleq{}i\mleq{}n  -  m  +  1\})


By


Latex:
(Assert  \mSigma{}\{if  m  +  i  +  1  \mleq{}z  m  then  (a  (m  +  i  +  1))  +  (b  (m  +  i  +  1))  else  a  (m  +  i  +  1)  fi 
              *  x\^{}m  +  i  +  1  |  0\mleq{}i\mleq{}n  -  m  +  1\}
              =  \mSigma{}\{(a  (m  +  i  +  1))  *  x\^{}m  +  i  +  1  |  0\mleq{}i\mleq{}n  -  m  +  1\}  BY
              ((BLemma  `rsum\_functionality`  THEN  Auto)  THEN  D  0  THEN  Reduce  0  THEN  Auto))




Home Index